Constitutional factors and risk of brain stroke development in women - I. N. Kukhareva; B. M. Doronin (Бюллетень сибирской медицины)
Morphofunctional characteristics were examined in old and middle-age women with ischemic stroke. The severity of the disease has been shown to be explained by the age-dependent deficiency of estrogen as one of risk factors.